A Case With New-Onset Neuromyelitis Optica Spectrum Disorder Following COVID-19 mRNA BNT162b2 Vaccination. Issue 3 (21st May 2022) - Caliskan, Ilay; Bulus, Eser; Afsar, Nazire; Altintas, Ayse
Abstract : Introduction: In the midst of the coronavirus disease of 2019 pandemic, active immunization by effective vaccination gained utmost importance in terms of global health. The messenger RNA (mRNA) vaccines are novel strategies requiring clinical surveillance for adverse events. Case Report: We report a 43-year-old previously healthy female with an optic neuritis attack 24 hours following immunization with the second dose of coronavirus disease of 2019 mRNA BNT162b2 vaccine. A second transverse myelitis attack together with an elevated anti-AQP-4 antibody titer confirmed the diagnosis of neuromyelitis optica spectrum disorder. Conclusion: Our case identifies the BNT162b2 vaccine as a possible trigger for neuromyelitis optica spectrum disorder. This rare and potentially coincidental event has no implications for vaccine administration practices. However, further research is needed to elucidate the effects of mRNA vaccines on humoral and cell-mediated immunity.